1981
DOI: 10.1139/b81-267
|View full text |Cite
|
Sign up to set email alerts
|

Germination of Thelephora terrestris basidiospores

Abstract: Thelephora terrestris basidiospores germinate slowly and sparsely on nutrient agar media if colonies of red yeast (Rhodotorula glutinis) or certain filamentous fungi are present together with the spores. Considerably faster germination at a higher percentage can be induced by seedling roots of pine and some other trees but not by roots of any herbs or grasses as yet tested. Germination is further improved if inhibitory compounds in the autoclaved agar medium are removed by means of activated charcoal. A conseq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

1984
1984
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…Our results indicate, therefore, that the germination response of R. luteolus spores is specific to host roots, although host species other than P. radiata may induce a similar response. This is in agreement with the results of Birraux & Fries (1981) with spores of T. terrestris.…”
Section: Stimulation Of Suillus Speciessupporting
confidence: 93%
See 1 more Smart Citation
“…Our results indicate, therefore, that the germination response of R. luteolus spores is specific to host roots, although host species other than P. radiata may induce a similar response. This is in agreement with the results of Birraux & Fries (1981) with spores of T. terrestris.…”
Section: Stimulation Of Suillus Speciessupporting
confidence: 93%
“…Four weeks after inoculation 34 and 31 % basidiospores of S. luteus and S. granulatus had germinated, respectively, while 46 % R. luteolus spores germinated under the same conditions. DISCUSSION Fries & Birraux (1980) and Birraux & Fries (1981) showed that when pine roots were placed on plates of nutrient agar seeded with basidiospores of the ectomycorrhizal fungi Hebeloma spp. and Thelephora terrestris Ehrh.…”
Section: Stimulation Of Suillus Speciesmentioning
confidence: 99%
“…All host plant genera that form ECM with Tt can associate with a much wider range of fungal associates, the highest specificity being found in the genus Alnus (Molina 1981;Miller et al 1991). Birraux and Fries (1981) suggested that host plant roots seemed to release one or several compounds which induced spore germination in Tt. Specificity between particular Tt isolates and host plants might explain, for example, why some workers have been unable to synthesise ECM between Tt and certain plant genera (e.g.…”
Section: Anatomy Of Ecmmentioning
confidence: 99%
“…Whereas most mature forest‐dominant EMF fail to colonize roots readily from spores, clearly T. sublilacina has this capability. While this had not been previously demonstrated, it was predictable on the basis of positive bioassays results (Baar et al ., 1999; Taylor & Bruns, 1999) and from the presence of this ability in related species, Tomentella crinalis (Kõljalg, 1992) and Thelephora terrestris (Birraux & Fries, 1981). This contrasts with earlier studies indicating that mature forest dominants rarely colonize seedlings from spores in unsterile soils (Deacon et al ., 1983; Fox, 1983).…”
mentioning
confidence: 99%